Event Locations in Extra-Familial Child Sexual Molestation Cases: The Istanbul Example - Gonultas, Burak M.; Sahin, Bahadir (SAGE PUBLICATIONS INC, 2018)
A great deal of attention has been devoted to sexual molestation cases, both in theory and in practice. Child molesters are versatile and are not easily identified. Various theories and tactics, the most contemporary of which is environmental criminology, have been developed to find those criminals. Locations of victims, crime scenes, and distances among them as well as other situational variables are used to predict possible future offences in environmental criminology. This study applies the theory to sexual molestation crimes in Istanbul. Dependent distance variables are found to be correlated with several situational variables in a selected sample of 127 extra-familial child sexual molestation cases.
Keywords: environmental criminology; sexual molestation cases in Istanbul; journey-to-crime; journey-to-victim; stranger criminals; MODUS-OPERANDI; ASSAULT VICTIMIZATION; MOBILITY PATTERNS; HUNTING PROCESS; SELF-CONTROL; OFFENDERS; ABUSE; HOMICIDE; OFFENSES; VIOLENCE; Criminology & Penology; Psychology